2010
DOI: 10.1097/ccm.0b013e3181d454b3
|View full text |Cite
|
Sign up to set email alerts
|

Catheter dysfunction and dialysis performance according to vascular access among 736 critically ill adults requiring renal replacement therapy: A randomized controlled study

Abstract: In terms of catheter dysfunction and dialysis performance among critically ill adults requiring acute renal replacement therapy, jugular site did not significantly outperform femoral site placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
4
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 33 publications
6
81
4
17
Order By: Relevance
“…In addition, the URR were comparable between routes. The results of this crossover design confirm those we found using a parallel design (7,8). Our findings are in accordance with new guidelines from the Centers for Disease Control and Prevention (11) for preventing central catheter infection, but contrast with the National Kidney Foundation's Kidney Disease Outcomes Quality Initiative Clinical Practice Guidelines for Vascular Access (6).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, the URR were comparable between routes. The results of this crossover design confirm those we found using a parallel design (7,8). Our findings are in accordance with new guidelines from the Centers for Disease Control and Prevention (11) for preventing central catheter infection, but contrast with the National Kidney Foundation's Kidney Disease Outcomes Quality Initiative Clinical Practice Guidelines for Vascular Access (6).…”
Section: Discussionsupporting
confidence: 80%
“…However, a parallel experiment from our group (7) showed that this might not be the case in ICU. In addition, the incidences of catheter bloodstream infections (7) or catheter dysfunction (8), as well as urea reduction ratios (URR) (8), were similar between randomized groups. Any unexpected result derived from a single study must be confirmed by other studies before translating evidence base into routine clinical practice.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, this is a single-center study and its findings may not apply to centers that prefer to use catheter insertion at other sites. We note that randomized controlled trials 18 show no difference in catheter dysfunction rate between jugular or femoral access. These observations support the view that the use of the femoral vein for CRRT is rational and justified, perhaps with the possible exception of obese patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The Cathedia study found lower rates of dysfunction in catheters placed in the RIJ, and femoral veins compared with the LIJ site. 26 Attention to both anticoagulation and line site may thus reduce interruptions.…”
mentioning
confidence: 99%